"Ain’t Got No Dream": Song Knowledge Mobilization for Queer Compassion Research - Joy, Phillip; Fewer, Stephen (Art/Research International)

(untitled) (University of Alberta, 2026)
"Ain’t Got No Dream" is a 3-minute song that incorporates findings from the Transformative Compassion project as a means of knowledge mobilization. The project explored the meanings of compassion for 2S/LGBTQ+ Canadians through semi-structured interviews. Data were analyzed through Foucauldian discourse analysis. Overall, findings suggest that compassion can open new possibilities for 2S/LGBTQ+ individuals within cis-heteronormative contexts. The song is inspired by the storytelling music of Dolly Parton and depicts the isolation and stigma that still exists for many people outside of the binary orientations of gender and sexuality.